2017
DOI: 10.2147/jpr.s133235
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pain and patient-controlled epidural analgesia-related adverse effects in young and elderly patients: a retrospective analysis of 2,435 patients

Abstract: In this retrospective study, data of 2,435 patients who received fentanyl and ropivacaine-based patient-controlled epidural analgesia (PCEA) for pain relief after elective surgery under general or spinal anesthesia were reviewed. Differences in postoperative pain, incidence of patient-controlled analgesia (PCA)-related adverse effects, and risk factors for the need for rescue analgesics for 48 hours postsurgery in young (age 20–39 years) and elderly (age ≥70 years) patients were evaluated. Although there were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 36 publications
1
27
0
1
Order By: Relevance
“…Compared with parenteral opioids, epidural analgesia provides better postoperative analgesia with less nausea, vomiting, and pruritus. However, some studies show that epidural anesthesia is associated with many adverse effects, such as urinary retention, hypotension, pruritus, and motor block. Among these, the main drawback of epidural anesthesia is inadvertent motor nerve block, which delays physical therapy and rehabilitation.…”
Section: Postoperative Analgesic Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with parenteral opioids, epidural analgesia provides better postoperative analgesia with less nausea, vomiting, and pruritus. However, some studies show that epidural anesthesia is associated with many adverse effects, such as urinary retention, hypotension, pruritus, and motor block. Among these, the main drawback of epidural anesthesia is inadvertent motor nerve block, which delays physical therapy and rehabilitation.…”
Section: Postoperative Analgesic Regimensmentioning
confidence: 99%
“…However, some studies show that epidural anesthesia is associated with many adverse effects, such as urinary retention, hypotension, pruritus, and motor block. Among these, the main drawback of epidural anesthesia is inadvertent motor nerve block, which delays physical therapy and rehabilitation. In addition, epidural anesthesia limits the options for postoperative prophylaxis against deep venous thrombosis.…”
Section: Postoperative Analgesic Regimensmentioning
confidence: 99%
“…(19), por lo que en la actualidad no se recomienda la analgesia epidural lumbar, excepto en obstetricia. Otro factor que puede contribuir a la elevada incidencia de bloqueo motor es el uso de una perfusión continua en lugar de la modalidad controlada por el paciente (PCA), que permite individualizar el tratamiento, adaptándose a las necesidades analgésicas de cada paciente, disminuyendo dosis y efectos secundarios (20).…”
Section:  Los Programas De Recuperación Intensificada (Enhanced Recounclassified
“…Koh et al investigated the incidence of adverse effects of epidural anesthesia in 2,435 postoperative patients in Korea, and found a high incidence of numbness and motor paralysis in young people (67.8%), while these were found in 11.5% of the elderly. Likewise, it was reported that low blood pressure is experienced by 3.1% of young people and 20.3% of the elderly after surgery, and that the incidence of hypotension and vomiting is higher in the elderly than in younger patients [8]. Therefore, a nonpharmacological method for relieving pain is desired.…”
Section: Introductionmentioning
confidence: 99%